Building CSR legitimacy through intercultural communication in Bula’s Community - Lusiana, Elnovani; Siti Khadijah, Ute Lies; Anwar, Rully Khairul; Ismail, Isma Rosila (PRofesi Humas, 2026)
Background: Corporate Social Responsibility (CSR), has often been viewed along the lines of technocratic compliance in the case of Bula, East Seram, an area of historical neglect and layered cultural diversity region. Technocratic Compliance sees CSR as little more than a box-ticking exercise, whereby the opportunity for real social community empowerment is lost. Purpose: The objective of this study is to propose an alternative pathway for CSR, which would involve the reframing of a socially bottomed phenomenon, ethnically and culturally integrated, from a prescriptive imposition  to an ethical, cross communicative practice of co-creation. Methods: The research poses a qualitative case study design. Data were integrated from the exercise of participant observation, document reviews, and semi-structured interviews with 15 informants, including representatives of the corporation, community leaders, and civil servants. This methodology enables the capturing of CSR phenomena from several perspectives. Results: Findings point to the generalized gap existing corporately centralized systems and community demands to be engaged in processes of collaboration and partnership. Interventions implemented in the absence of cultural dialogue are, at best, likely to interact with bureaucratic functions and survive as indifference. In contrast, initiatives designed and implemented in partnership demonstrated prevalence to social support and sustainable change. Conclusion: The study states that the legitimacy of CSR is not a function of positive legal prescription, but rather an outcome of meaningful, sustained dialogues across cultures. Implications: This research improves the understanding of CSR as a type of “social diplomacy.” It suggests that companies should treat philanthropic acts as more than a transaction, creating and sustaining culturally adaptive communications that respect local knowledge and promote a more just and more balanced industry-society relationship.